GAMBARAN TINGKAT KEPUASAN LANSIA TERHADAP PELAYANAN POSYANDU LANSIA - Tamsuri, Anas; Arismadani, Yanuar Dwi (Akademi Keperawatan Pamenang, 2014)
Aged satisfaction towards service quality in health care center for mothers and babies is influenced by many factors real evidence (tangible), reliability (reliability/trustworthy), responsiveness and assurance (certainty). These things must be fulfilled by officials or cadres of health care center for mothers and babies (Posyandu) in order to satisfied all targets. The purpose of this research was to know the level of mother satisfaction about the quality of Aged health care center for mothers and babies (Posyandu) health services in health care center for mothers and babies (Posyandu) Pendawa Dusun Suren Desa Jambu Kecamatan Kayen Kidul Kabupaten Kediri.The design of research that used is descriptive. The population is all the aged mothers 30 respondents was taken with a total sampling technique. Research variable is the level of aged satisfaction toward health care center for aged (Posyandu Lansia) health services collected by using questionnaire with 25 questions. The data that produced is processed by means of editing, cording, scoring, tabulating and analyzed by percentage. The data presented in the form of diagrams and tables.From the results of research, almost half of respondents rate the quality of service in Aged Posyandu reviewed from tangible including satisfactory and very satisfactory it is 15 respondents (50 %), from reliability the majority is satisfactory it is 17 respondents (56.7 %), of the responsiveness the majority is satisfactory it is 19 respondents (63.3 %), from the assurance, a half is satisfactory it is 15 respondents (50 %), from the empathy, a half is satisfactory it is 15 respondents (50 %) and in general most of the respondents are satisfied about 21 respondents (70 %) of a total of 30 respondents.This is caused by physique facilities of health care center for mothers and babies (Posyandu) are adequate, the officer gave service with a friendly, courteous, responsive, professional and reliable.It was concluded that the quality of service in health care center for mothers and babies (Posyandu) Pendawa Dusun Suren Desa Jambu Kecamatan Kayen Kidul Kabupaten Kediri has been rated satisfactory. It is suggested that existing services must be maintained. Keywords : satisfaction, service quality of aged posyandu